2019
DOI: 10.1159/000498844
|View full text |Cite
|
Sign up to set email alerts
|

Monotypic IgG1-kappa Atypical Anti-Glomerular Basement Membrane Nephritis: A Case Report

Abstract: Anti-glomerular basement membrane (anti-GBM) glomerulonephritis is a rare disease caused by autoantibodies against the glomerular basement membrane. Atypical anti-GBM nephritis is clinically less aggressive and characterized by the absence of circulating autoantibodies to the basement membrane. A previously healthy 53-year-old white woman presented with a rising creatinine over a short observation period. Renal biopsy, urinary sediment, and laboratory testing confirmed the diagnosis of atypical anti-GBM diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The patient's renal function improved and remained stable at 3 months follow up. [5] Coley et al, reported the case of a 53-year-old man with decreased kidney function following an upper respiratory tract infection. He was also found with microscopic hematuria and nonnephrotic range proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient's renal function improved and remained stable at 3 months follow up. [5] Coley et al, reported the case of a 53-year-old man with decreased kidney function following an upper respiratory tract infection. He was also found with microscopic hematuria and nonnephrotic range proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Olivier et al. 5 has described a 53-year-old woman who presented with rapidly worsening serum creatinine and whose biopsy examination revealed linear staining along GBMs by monotypic IgG1-kappa. Serum anti-GBM antibodies were negative by ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…958 There are several case reports of patients with anti-GBM disease who were successfully treated with mycophenolate or MPA instead of cyclophosphamide. [959][960][961][962] Mycophenolate could be used instead of cyclophosphamide in patients who refuse cyclophosphamide or are intolerant of cyclophosphamide because of its toxicity.…”
Section: Rationalementioning
confidence: 99%
“…890 There are several case reports of patients with anti-GBM disease successfully treated with mycophenolate or MPA instead of cyclophosphamide. [891][892][893][894] Mycophenolate could be used instead of cyclophosphamide in patients refusing cyclophosphamide, or intolerant of cyclophosphamide because of its toxicity.…”
Section: Table Agbm1 Treatment Of Anti-gbm Diseasementioning
confidence: 99%